The recent WHO guideline on acute malnutrition overestimates therapeutic energy requirement - Harshpal Singh Sachdev; Anura V. Kurpad (Elsevier, 2024)
Summary: The World Health Organization has recently updated the guideline on the prevention and management of wasting and nutritional oedema (acute malnutrition) in infants and children under 5 years. Apart from differences with regard to the nutritional framework that defines the quantity of energy required as Ready-to-Use Therapeutic Food (RUTF) for the outpatient treatment of severe wasting and/or nutritional oedema, there are also important gaps in the practical guidance. Instead of the recommended energy intake of 150-185 kcal/kg/day, our alternative calculations indicate the requirement to be only 105-120 kcal/kg/day. If true, the implementation of such caloric overfeeding can have adverse consequences. Gaps in practical guidance also need to be addressed, including the timing of transition to home-based diets, maximal duration of therapeutic feeding, especially in non-responders (∼50% in South Asia), and the role of augmented home foods as the primary therapeutic food option.